Mathematics in the Tradition of Nusantara Architecture: An Effort to Improve Students’ Problem-Solving Skills - Netriwati, Netriwati; Lestari, Ita Dwi; Emilia, Wulan; Mulani, Al Qausar; Nendra, Fadly (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Previous research has explored students' problem-solving abilities, yet few studies have incorporated elements of Nusantara architecture into the mathematics learning process. This study aims to examine the changes in students’ problem-solving skills following the implementation of Nusantara architecture-based learning in the topic of number patterns. This approach is operationalized through the utilization of carving motifs, symmetrical structures of traditional buildings, and construction rhythms as concrete representations of number pattern concepts. The research employed a one-group pretest–posttest design, involving 33 eighth-grade students from SMP Negeri 7 Bandar Lampung as participants. The research instruments consisted of a problem-solving ability test and a student response questionnaire, while the learning process was conducted over four meetings. Because the data did not meet the assumption of normality, the analysis was conducted using the Wilcoxon Signed Rank Test and N-gain calculations to determine the magnitude of improvement in learning outcomes. The results of the analysis showed a significance value of 0.000 < 0.05, indicating a significant difference between the scores before and after the treatment. The N-gain value of 0.7700 falls into the high category, indicating that Nusantara architecture–based learning is able to improve students’ mathematical problem-solving abilities. In addition, the questionnaire results showed that most students gave positive responses to the implementation of this learning approach. Overall, Nusantara architecture–based learning has been proven effective in strengthening students’ understanding of mathematical concepts and providing a more contextual, creative, and culturally grounded learning experience.